Объяснение:
{k + m - 3k + 3m = 18
{2k - m - 6k + 4m = -120
{-2k + 4m = 18
{-4k + 3m = -120
m = (4k:3) - 40
-2k + (16k : 3) - 160 = 18
-6k + 16k - 480 = 54
10k = 534
k = 53, 4
-106,8 + 4m = 18
m = 31,2
не уверен, но решать надо примерно так
ответ:k=15
m=12
Думаю правильно, если это проходите
Объяснение:
{k + m - 3k + 3m = 18
{2k - m - 6k + 4m = -120
{-2k + 4m = 18
{-4k + 3m = -120
m = (4k:3) - 40
-2k + (16k : 3) - 160 = 18
-6k + 16k - 480 = 54
10k = 534
k = 53, 4
-106,8 + 4m = 18
m = 31,2
не уверен, но решать надо примерно так
ответ:k=15
m=12
Думаю правильно, если это проходите
Объяснение: